Penyuluhan Strategi Komunikasi Tokoh Masyarakat Dalam Menyelesaikan Konflik Sengketa Tanah di RW 02 Desa Tarai Bangun Kecamatan Tambang Kabupaten Kampar (STMIK Dharmapala Riau, 2024)
Land disputes or can also be said to be land rights disputes, namely the emergence of legal disputes that originate from a complaint from a party (person or entity) containing objections and demands for land rights, both regarding land status, priority and ownership in the hope of getting obtain administrative settlement in accordance with applicable regulatory provisions. This Community Service aims to provide an understanding of community leaders' communication strategies carried out by community leaders including methods or mechanisms for resolving conflicts from various reviews to determine the strategies used in resolving conflicts through conciliation, negotiation and mediation in land dispute conflicts in RW 02 Tarai Bangun Village Kampar Regency.